Strategi Mitigasi Resiko Keamanan Rantai Pasokan Tandan Buah Segar Pabrik Kelapa Sawit Menggunakan Pendekatan Fuzzy dan ISO 28001 - Hermawan Thaheer; Sawarni Hasibuan (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2019)
The release of ownership of oil palm plantation land at SEI Kencana from PT Perkebunan Nusantara V (PTPN V) Republic of Indonesia covering an area of 2800 ha has affected the planned supply of Fresh Fruit Bunch (FFB) raw materials to the company's palm oil industry. The supply from the SEI Kencana is calculated to be reduced by 50%, so it must be fulfilled from the company's external parties. There are at least five aspects of risk estimated to affect the supply of FFB, namely aspects of raw material supply, aspects of quality FFB supply, aspects of FFB prices, management aspects, and social aspects. Overall there are 16 identified risks in the FFB supply chain. The analysis uses fuzzy weighting techniques, followed by characterization using the principle of ISO 28001, grouping risks into three, namely: 1) risks that must be addressed immediately, 2) risks that are considered to be handled, and 3) risks that are temporarily noted (documentation). The risks with characters being addressed and considered to be addressed are those risks which in the near future, are considered to affect the supply of FFB raw materials for the industry. In the case of the release of 2800 ha of land in PTPN V, the amount of risk that needs to be mitigated with documented risk is equal. Within the next five years, mitigation of these risks has been prepared. With this risk management, the supply of FFB to factories in the Rokan-Tandun district can be secured.